Andhap Asor among Early Adult Women from Broken Homes: A Cultural Perspective on Emotional Regulation - Peristianto, Sheilla Varadhila; Mufti, Ismi Darojatun (Universitas Muhammadiyah Surakarta, 2025)
This study explores the role of Andhap Asor, a Javanese cultural value emphasizing humility and emotional restraint, as a coping mechanism for early adult women from broken home families. Using a qualitative approach with an intrinsic case study design, the research involved four Javanese women aged 20–30 who had experienced parental separation. Data were collected through semi-structured in-depth interviews, field notes, and non-participant observation, and analyzed using thematic analysis. Findings reveal four primary emotional regulation patterns: acceptance, suppression, distraction, and resilience. These strategies were deeply influenced by the internalization of Andhap Asor, which provided participants with a cultural framework to reinterpret emotional pain into personal growth. The value of Andhap Asor enabled participants to respond to emotional adversity with self-reflection, patience, and spiritual meaning—rather than with resentment or reactive behaviors. Thus, Andhap Asor serves as both an internal and social emotional regulation strategy, fostering psychological resilience and supporting interpersonal harmony. These findings highlight the significance of incorporating culturally grounded approaches in psychological interventions, particularly for individuals coping with the emotional impacts of family dysfunction.